An uncommon anatomic variation of the sartorius muscle in a domestic dog (Canis lupus familiaris) - Viegas, Katia Aparecida da Silva; Fogaça, Jessica Leite; Nunes, Adriane Lauro; Leal, Rodrigo; Silva , Ellen Satilio da; Machado , Vania Maria de Vasconcelos; Filadelpho, André Luis (Acta Scientiarum. Biological Sciences, 2023)
The sartorius muscle is located in the pelvic limb of the dog and is divided into a cranial and caudal part. There is no report describing of the three parts of the sartorius muscle. The aim of the present report was to describe the presence of a third part of the sartorius muscle in a dog. Although it does not represent a malformation, it is an important anatomical variation to consider for didactic purposes of dissection and in surgeries of the pelvic limb, as in this case there is a need to move the muscles apart to maintain their integrity. Furthermore, this anatomical description is relevant for comparative purposes in this animal species.